Community-Based Management and Sustainable Harvesting of Mormyridae Species in the Congo River Basin - Victorine, Mbadu (Global Writing Academica Researching and Publishing, 2023)
The Mormyridae species, known for their ecological and economic significance, are vital to the biodiversity and livelihoods within the Congo River Basin. This study explores the effectiveness of community-based management approaches in ensuring the sustainable harvesting of these species. By integrating traditional knowledge with modern conservation practices, this research assesses the involvement of local communities in the management of Mormyridae fisheries and the impact of these practices on fish populations and biodiversity. Data were collected through field surveys, interviews with local fishermen, and analysis of existing literature on sustainable fisheries management. The findings reveal that community engagement is crucial for the success of conservation efforts, as locally-driven initiatives are more adaptable to the environmental and socio-economic conditions of the region. However, challenges such as limited resources, lack of formal training, and external economic pressures pose significant barriers to effective implementation. The study concludes with recommendations for enhancing community-based strategies, emphasizing the need for stronger policy support and capacity-building programs to ensure the long-term sustainability of Mormyridae fisheries in the Congo River Basin.